Potential biodiesel-producing microalgae: two new strains of Amphikrikos sp. Issue 5 (9th April 2017) - Han, Jichang; Zhang, Lin; Wang, Pu; Wang, Song; Yang, Guanpin; Zhao, Lu; Pan, Kehou
ABSTRACT: BH32 and BH43 were isolated and identified as Amphikrikos sp. based on morphological characteristics and phylogenetic trees. They shared the same 18S rRNA sequences, but possessed different amounts of introns in their 18S rDNAs. The specific growth rate, cellular component and fatty acid profile under different growth stages have been surveyed. Their main fatty acids were found to be C16 and C18 groups. Our results indicated that both of them could be taken as excellent candidates of biodiesel. Moreover, the intra-genus polymorphism of 18S rDNA caused by intron presence/absence can provide valuable information for the study of intron evolution.